Analisis Kredit Bermasalah pada Mandala Multifinance Tbk Karawang - Silvia Indriyani; Sihabudin; Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Mandala Multifinance Tbk Karawang is a leasing company that helps customers in obtaining financing for capital needs. Therefore, any distribution of credit should be well monitored by the management of the company so that the credit is not abused. The study aims to analyze problematic credit and find out the application of the 5C principle in the granting of credit that affects the level of NPL (Non Performing Loan) on the Mandala Multifinance Tbk Karawang. The method applied uses qualitative data with a triangulation approach, which includes the collection of primary data through observations, interviews, and documentation. The Non-Performing Loan (NPL) financial ratio is used as a tool for analyzing data. The results of the research show that the application of the 5C principle in the distribution of credit in Mandala Multifinance Tbk Karawang is still ineffective because there are shortcomings in the analysis process carried out. The conclusion of this study is that the highest NPL ratio in 2021 is 4.35, while the lowest in 2020 is 3.32. The average NPL for the three years 2020-2022 was 3.74, marking a healthy category.